Improved Murine Blastocyst Quality and Development in a Single Culture Medium Compared to Sequential Culture Media. (March 2016) - Hennings, Justin M.; Zimmer, Randall L.; Nabli, Henda; Davis, J. Wade; Sutovsky, Peter; Sutovsky, Miriam; Sharpe-Timms, Kathy L.
Objective: Validate single versus sequential culture media for murine embryo development. Design: Prospective laboratory experiment. Setting: Assisted Reproduction Laboratory. Animals: Murine embryos. Interventions: Thawed murine zygotes cultured for 3 or 5 days (d3 or d5) in single or sequential embryo culture media developed for human in vitro fertilization. Main Outcome Measures: On d3, zygotes developing to the 8 cell (8C) stage or greater were quantified using 4', 6-diamidino-2-phenylindole (DAPI), and quality was assessed by morphological analysis. On d5, the number of embryos reaching the blastocyst stage was counted. DAPI was used to quantify total nuclei and inner cell mass nuclei. Localization of ubiquitin C-terminal hydrolase L1 (UCHL1) and ubiquitin C-terminal hydrolase L3 (UCHL3) was reference points for evaluating cell quality. Results: Comparing outcomes in single versus to sequential media, the odds of embryos developing to the 8C stage on d3 were 2.34 time greater ( P = .06). On d5, more embryos reached the blastocyst stage ( P = <.0001), hatched, and had significantly more trophoblast cells ( P = .005) contributing to the increased total cell number. Also at d5, localization of distinct cytoplasmic UCHL1 and nuclear UCHL3 was found in high-quality hatching blastocysts. Localization of UCHL1 and UCHL3 was diffuse and inappropriately dispersed throughout the cytoplasm in low-quality nonhatching blastocysts. Conclusions: Single medium yields greater cell numbers, an increased growth rate, and more hatching of murine embryos. Cytoplasmic UCHL1 and nuclear UHCL3 localization patterns were indicative of embryo quality. Our conclusions are limited to murine embryos but one might speculate that single medium may also be more beneficial for human embryo culture. Human embryo studies are needed.